Protocolo de assistência ventilatória mecânica em pacientes com neoplasias oncohematológicas e insuficiência respiratória aguda - Lidia Miranda Barreto Mourao (2018)
Introduction: Acute respiratory failure (ARF) is one of the main causes of transference of oncohaematological patients to intensive care units (ICUs). As in other patient groups, noninvasive mechanical ventilation (NIMV) has been changing the outcomes related to the evolution of respiratory dysfunction and conduction of clinical treatment in this population. However, the predictors of NIMV success or failure in these patients are not well defined. In addition, there is doubt whether the association of failure with NIMV with worse outcomes occurs independently of the greater severity observed in patients who fail in this mode of ventilatory assistance. Objective: To propose and evaluate the performance of a ventilatory assistance protocol in oncohematologic patients admitted to the ICU with acute respiratory dysfunction. Methods: intervention study to test the oxygenation index based protocol (OI) as the main decision-making tool for the mode of mechanical ventilation in patients with hematologic malignancies admitted in ICU. On admission, according to the OI, the patient may receive supplemental oxygen (flow set according to the demand of the patient), or NIMV invasive mechanical ventilation (IMV). Patient recruitment was performed in an ICU of a university hospital from January / 2015 to January / 2018. Clinical, demographic, laboratory and severity scores were collected on admission and monitored during hospitalization. The characteristics associated with NIMV failure were evaluated, as well as the association of failure to this mode of ventilatory support with relevant clinical outcomes, such as length of hospital stay and mortality. Results: A total of 82 patients were included, mean age 52.1 ± 16 years, and 44 (53.6%) were male. At inclusion in the study, six patients (7.3%) received IMV, 59 (89.7%) received NIMV and 17 (20.7%) received oxygen therapy. The ICU mortality was higher in the group initially undergoing intubation and IMV (83.3%) than the initial NIMV group (49.2%) and oxygen (5.9%) (p <0.001). There was no significant difference between groups when hospital mortality (p = 0.326) and outpatient mortality (p = 0.284) were considered. There was no statistically significant difference in NT-pro BNP serum levels among the three groups studied (p = 0.711). When considering only the subgroup under NIMV (n = 59), there was no difference in NT-pro BNP serum levels among patients who failed or were successful in this mode of ventilatory care (p = 0.516). Of the 59 patients initially receiving NIMV, 30 (50.8%) failed this ventilatory support and were intubated: 23 patients (76.6%) failed in the first 12 hours, five patients (16.7%) between 12 and 24 hours and two patients (6.7%) after 24 hours of admission. Patients who failed on NIMV used vasopressors more frequently (90% vs 27.5%, p <0.001); the use of vasopressors was independently associated with failure of NIMV in multivariate analysis (p <0.001; OR: 1.95, 95% CI: 1.61-2.36) adjusted for variables sepsis on admission, SOFA, C-reactive protein (P <0.001, OR: 1.62, 95% CI: 0.49-0.77), after adjusting for use in the intensive care unit (ICU). vasopressors, sepsis on admission, lactate on admission, oxygenation index (OI), and respiratory rate (RR) on admission. In the same way, hospital mortality was higher among patients who failed (p = 0.049, OR: 1.29, 95% CI: 0.61-0.99), adjusted for lactate, OI and RR. Survival at 12 months was higher among patients who were successful than those who failed at NIMV (p <0.001, OR: 1.32, 95% CI: 0.74-0.98) after adjusting for OI and RR. Conclusion: The performance of the proposed protocol was satisfactory, with an absolute reduction of the frequency of failure by 18% (50.8%) in relation to the historical controls of the unit (68.4%) to long term. Some variables present at admission and observed during hospitalization the use of vasopressors may be useful to predict failures to this support during the clinical conduction of the patient. The identification of the good candidates for NIMV among onco-hematologic patients with acute respiratory dysfunction is of extreme importance to avoid inadequate delays in intubation.